1998
DOI: 10.1103/physrevb.58.10389
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electronic properties ofFeSi2

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
68
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 26 publications
(17 reference statements)
9
68
0
3
Order By: Relevance
“…In Fig. 4 [193][194][195][196][197] has confirmed the decrease in B(M1) with increasing angular momentum [11]. This constitutes the strongest argument in favor of the shears mechanism in lead nuclei.…”
supporting
confidence: 74%
“…In Fig. 4 [193][194][195][196][197] has confirmed the decrease in B(M1) with increasing angular momentum [11]. This constitutes the strongest argument in favor of the shears mechanism in lead nuclei.…”
supporting
confidence: 74%
“…Therefore, electronic structure and optical property of β-FeSi2 epitaxial films are considered to be modified by the strain induced at the heteroepitaxial interface of β-FeSi2/Si. The strain effects on the electronic structure have been investigated by first principle calculations [4][5][6][7][8], but there have been no experimental result about the modification of electronic structure. In our recent studies, we have investigated lattice deformations and direct transition energies (Eg) in β-FeSi2 epitaxial films grown on Si(111) substrate, and revealed that the Eg shifted to lower energy by the lattice shrinkage induced by thermal annealing [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…7 Moreover, this band gap has a high sensitiveness to lattice distortions and it is expected that the presence of suitable strain fields will make it possible to transform it into a direct one with a strong oscillator strength. 8,9 From this point of view, the study of the formation of isolated nanoparticles will be of interest to explore that prediction and additionally to complement low-dimensional structure knowledge for optoelectronic applications. Previous experiments by Grimaldi et al 10 and Martinelli et al 11 showed that elastically strained ball-shaped particles ͑formed by ion-beam synthesis͒ surrounded by a defect-free matrix do not have luminescence properties, whereas unstrained disk-shaped particles in a matrix with a large number of defects emit around 0.805 eV.…”
Section: Introductionmentioning
confidence: 99%
“…In the process we tested the band gap conversion-indirect to direct when the nanoparticles are under strain. 8,9 In Sec. II we describe the experimental procedures.…”
Section: Introductionmentioning
confidence: 99%